Pengembangan Taman Sentyaki untuk Aktivitas Sosial Ekonomi Inklusif - Salsabila Ananda Batubara; Wakhidah Kurniawati; Johanes Adhi Nugroho (Jurnal Riptek, 2026)
Sentyaki Park in North Semarang, designated as a Free Activity Zone, currently faces significant development challenges, including limited accessibility for vulnerable groups, insufficient infrastructure, and poor environmental management that results in frequent inundation. This study aims to strategically revitalize the park into a truly inclusive, sustainable, and multi-functional public amenity by applying the principles of Placemaking. The research methodology combines SWOT Analysis with comprehensive activity and site analysis, synthesized within the LIFE Concept (Local Economic Activation, Inclusive Social Interaction, Free Public Access, Eco-Friendly) framework. The findings suggest that transforming Sentyaki Park requires enhancing its spatial identity through an integrated design that maximizes social interaction and economic potential. The resulting revitalization plan proposes clear spatial programming for community activities and supports local economic growth, while also integrating nature-based solutions to enhance environmental resilience. The culmination of this research is the implementation of a 3D design visualization, which provides a concrete and integrated model for the park's future development. This research demonstrates that the application of Placemaking, guided by the multi dimensional LIFE Concept, offers a robust approach to creating a just, functional, and socio-economically vital public space.